Impacts of Epigenetic Processes on the Health and Productivity of Livestock - Wang, Mengqi; Ibeagha-Awemu, Eveline M. (Frontiers in Genetics, 2021)
The dynamic changes in the epigenome resulting from the intricate interactions of genetic and environmental factors play crucial roles in individual growth and development. Numerous studies in plants, rodent and human have provided evidence of the regulatory roles of epigenetic processes in health and disease. There is increasing pressure to increase livestock production in light of increasing food needs of an expanding human population and environment challenges, but there is limited related epigenetic data on livestock to complement genomic information and support advances in improvement breeding and health management. This review examines the recent discoveries on epigenetics processes due to DNA methylation, histone modification and chromatin remodeling and their impacts on health and production traits in farm animals, including bovine, swine, sheep, goat and poultry species. Most of the reports focused on epigenome profiling at the genome wide or specific genic regions in response to developmental processes, environmental stressors, nutrition and disease pathogens. The bulk of available data mainly characterized the epigenetic marks in tissues/organs or in relation to traits and detection of epigenetic regulatory mechanisms underlying livestock phenotype diversity. However, available data is inadequate to support gainful exploitation of epigenetic processes for improved animal health and productivity management. Increased research effort, which is vital to elucidate how epigenetic mechanisms affect the health and productivity of livestock is currently limited due to several factors including lack of adequate analytical tools. In this review, we: (1) summarize available evidence of the impacts of epigenetic processes on livestock production and health traits; (2) discuss the application of epigenetics data in livestock production; and (3) presents gaps in livestock epigenetics research. Knowledge of the epigenetic factors influencing livestock health and productivity is vital for management and improvement of livestock productivity.